2022
DOI: 10.1186/s12944-022-01655-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of LDL:HDL ratio with prediabetes risk: a longitudinal observational study based on Chinese adults

Abstract: Background Low-density lipoprotein:high-density lipoprotein cholesterol ratio (LDL:HDL ratio) has a good performance in identifying diabetes mellitus (DM) and insulin resistance. However, it is not yet clear whether the LDL:HDL ratio is associated with a high-risk state of prediabetes. Methods This cohort study retrospectively analyzed the data of 100,309 Chinese adults with normoglycemia at baseline. The outcome event of interest was new-onset pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…According to a study, determining insulin resistance can be done with high accuracy using the lowdensity lipoprotein/high-density lipoprotein cholesterol ratio (LDL/HDL ratio) (Zhang, et al, 2015). Another study found that the risk of prediabetes is positively connected with an elevated LDL/HDL ratio (Kuang, et al, 2022). All of these results suggested that the LDL:HDL ratio might be a reliable indicator of blood glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study, determining insulin resistance can be done with high accuracy using the lowdensity lipoprotein/high-density lipoprotein cholesterol ratio (LDL/HDL ratio) (Zhang, et al, 2015). Another study found that the risk of prediabetes is positively connected with an elevated LDL/HDL ratio (Kuang, et al, 2022). All of these results suggested that the LDL:HDL ratio might be a reliable indicator of blood glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, testing of the parameters of cholesterol is essential to determine CVD risk in the population. A retrospective cohort study done among the Chinese population, reported that an increase in LDL:HDL ration indicated an increased risk of prediabetes, among women, family history of diabetes, younger population and non-obese people (7).…”
Section: Introductionmentioning
confidence: 99%
“…A case‒control study indicated that the LDL-C/HDL-C ratio was the main risk factor for ischemic strokes [ 20 ]. Kuang et al [ 21 ] found that the LDL-C/HDL-C ratio also has some value in prediabetes risk assessment, and the accuracy was better than that of LDL-C and HDL-C. However, their predictive value is often applied only to subgroups of the whole population, such as nonobese people with normal lipids and patients with nonvalvular atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%